2014
DOI: 10.1155/2014/381719
|View full text |Cite
|
Sign up to set email alerts
|

InvestigatinghspGene Expression in Liver ofChanna striatusunder Heat Stress for Understanding the Upper Thermal Acclimation

Abstract: Changes in hsp gene expression profiles in murrel Channa striatus experimentally exposed to temperature stress (36°C) for 4, 15, and 30 days were investigated; fish collected from aquaculture ponds and maintained in laboratory at the pond temperature (25 ± 1°C) served as control. Channa collected from a hot spring runoff (36°C) was included in the study to examine the hsp profiles beyond 30 days of exposure. Gene expression analyses of a battery of hsps in liver tissues were carried out by quantitative RT-PCR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 39 publications
4
27
0
Order By: Relevance
“…In the current study, upregulation of HSP70 was induced by heat treatment according to previous report (Mizushima et al 2000). It has been demonstrated that HSP70 expression continues to increase with duration of exposure, while HSP90 and HSP110 increase to a much higher level and then decrease and HSP27 and HSP47 fail to be affected under heat stress (Purohit et al 2014). Meanwhile, we also found that Trichinella spiralis infection inhibited HSP70 expression, indicating that HSP70 plays a key role in post-infection irritable bowel syndrome.…”
Section: Discussionsupporting
confidence: 77%
“…In the current study, upregulation of HSP70 was induced by heat treatment according to previous report (Mizushima et al 2000). It has been demonstrated that HSP70 expression continues to increase with duration of exposure, while HSP90 and HSP110 increase to a much higher level and then decrease and HSP27 and HSP47 fail to be affected under heat stress (Purohit et al 2014). Meanwhile, we also found that Trichinella spiralis infection inhibited HSP70 expression, indicating that HSP70 plays a key role in post-infection irritable bowel syndrome.…”
Section: Discussionsupporting
confidence: 77%
“…The immunological properties of HSPs enable them to be used in new immunotherapies of cancers and infections [16]. The elevated expression of HSPs is considered to be a universal response to adverse conditions, representing a potential b-actin KM091925 mechanism of cellular defence against disease and a potential target for novel therapeutics [27,41]. Significant increase in expression was observed in case of HSP60 (>2 fold) and HSP90 (0.7 fold) genes ( Fig.…”
Section: Effect Of Arsenic On Hsp Gene Expressionmentioning
confidence: 99%
“…These included genes related to hyper-and hypo-osmotic stress (Kalujnaia et al 2007;Evans and Somero 2008;Laverty and Skadhauge 2012), heat stress (Fangue et al 2006;Purohit et al 2014), hypoxia and oxidative stress (Almeida et al 2002;Woo et al 2013) (see Table S1 for the complete list of genes). Additionally, we investigated the expression levels of the entire set of genes of the ornithine-urea cycle (OUC) pathway: N-acetylglutamate synthase (NAGS), ornithine carbamoyl transferase (OTC), carbamoyl-phosphate synthase III (CPSIII), argininosuccinate synthase (ASS), argininosuccinate lysase (ASL), and arginase (ARG), and one accessory urea pathway gene (ornithine glutamine synthetase (GS)) ( Table 2).…”
Section: Survey Of Published Stress-response Genes Among Degs and Urementioning
confidence: 99%
“…This phenomenon is best understood in the context of genetic assimilation, in which genes and consequently traits that are unconditionally adaptive become genetically fixed (canalized) such that they may continue to be expressed long after the stressor has been removed (Stearns 1994;Badyaev 2005;Lande 2009). Several studies suggest that constitutive up-regulation (transcriptome uploading) of stress-responsive genes may actually represent a major phenomenon in animals evolved under chronic environmental stress (Latta et al 2012;Purohit et al 2014). For instance, Trematomus bernacchii (family Nototheniidae) and several other Antarctic fishes have been shown to have lost the ability to induce heat shock proteins but constitutively express heat shock proteins (Buckley et al 2004;Shin et al 2014).…”
Section: Gene Expression Changes In a Grahamimentioning
confidence: 99%
See 1 more Smart Citation